Optimization of Restorative Justice in the Resolution of Minor Criminal Cases at the District Prosecutor's Office - Bimo Widyatmoko; Hartoyo Hartoyo; Sri Sukmana Damayanti (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2026)
Purpose: This study aims to analyse the implementation, effectiveness, and optimization of Restorative Justice in resolving minor criminal cases at the District Prosecutor’s Office. It also examines how restorative justice principles are applied in practice and assesses their contribution to more efficient, fair, and balanced case resolution within the criminal justice system. Research Methodology: This research employs an empirical juridical method using statutory, case, and conceptual approaches. It examines legal norms and their practical implementation in case handling at the District Prosecutor’s Office. The data are analysed qualitatively to understand restorative justice practices and their effectiveness in resolving minor criminal cases. Results: The findings indicate that RJ implementation of Restorative Justice has been conducted in accordance with the Regulation of the Attorney General of the Republic of Indonesia Number 15 of 2020 through a reconciliation mechanism between victims and offenders facilitated by prosecutors. Conclusions: Optimization efforts should include enhancing prosecutors’ competencies, strengthening inter-agency coordination, improving regulations, and increasing public awareness through socialization programs. Supporting factors include a clear legal framework, commitment from the Prosecutor’s Office, and a culture of deliberation within society. Limitations: Restorative Justice serves as an effective and equitable alternative for resolving minor criminal cases and is consistent with modern criminal law principles. Key supporting factors include a clear legal framework, institutional commitment, and a societal culture valuing deliberation and consensus. Contributions: Future studies are encouraged to broaden the scope of research and examine the long-term effects of Restorative Justice on victim satisfaction, offender reintegration, and recidivism reduction.